A191 THE SAFETY AND FEASIBILITY OF ENDOSCOPIC ULTRASOUND-GUIDED PARENCHYMAL LIVER BIOPSY AT A LARGE COMMUNITY HOSPITAL. (1st March 2018) - Rombaoa, C; Chen, A
Abstract: Background: Parenchymal liver biopsy is important for diagnosis and management for many liver disease patients. Percutaneous image-guided liver biopsy is currently the most widely used method; however, endoscopic ultrasound (EUS)-guided liver biopsy with newer flexible large-bore core needles represents an emerging approach for sampling. EUS-guided liver biopsy (EUS-LB) offers certain advantages over traditional methods such as doppler assistance to avoid intervening vessels and the ability to image both hepatic lobes to minimize sampling error. Aims: Our aim is to evaluate the feasibility and safety of EUS-LB in obtaining adequate tissue samples for diagnosis of unexplained liver disease and to compare our results to percutaneous liver biopsy at our institution. Methods: We conducted a retrospective chart review of patients who underwent EUS-LB at Santa Clara Valley Medical Center in San Jose, California between January 1 and September 30, 2017. All patients who underwent EUS-LB had 2 passes taken. For comparative purposes, we also identified patients who underwent a percutaneous liver biopsy for similar indications. We collected data on procedure duration, adverse events, complete portal tracts (CPTs), inflammation grade, and fibrosis grade. Results: To date, there have been 8 patients who have undergone EUS-LB with a 19-gauge Acquire needle (Boston Scientific) at our institution. The indications for EUS-LB included unexplained abnormal LFTs (n=6), staging of hepatitis B (n=1), and cirrhosis of unclear etiology (n=1). The average procedure duration for EUS-LB and percutaneous liver biopsy was 19 minutes and 28 minutes, respectively. The average number of CPTs was 9.4 (range 6–13) and 9.1 (range 6–14), respectively. Three-quarters of patients in the EUS-LB group were determined to have mild inflammation (6/8, 75%). Most patients had 0 stage of fibrosis (7/8, 87.5%). Recovery time for EUS-LB patients averaged 30 minutes while percutaneous liver biopsy patients were all placed in observation for 240 minutes prior to discharge. No patients experienced any adverse events. Conclusions: EUS-LB is feasible, safe, and produces a comparable sample adequacy for histologic examination compared to percutaneous liver biopsy at our community hospital. In addition, EUS-LB requires less time to complete, both in procedure time and recovery time. Further study regarding EUS-LB is warranted for optimal technique (e.g. the use and amount of suction) as well as direct comparison to percutaneous approach in terms of possible cost reduction and improved patient satisfaction. Funding Agencies: None